The capital structure of Finnish biotechnology SMEs: An empirical analysis - Antti-Jussi Tahvanainen (The Research Institute of the Finnish Economy (ETLA), 2003)
This empirical study tests three different theoretical frameworks of capital structure choice on a cross-sectional data of 59 Finnish biotechnology SMEs. The theoretical approaches comprehend principal-agent, asymmetric information and trade-off theories. The purpose of the paper is to trial the validity of the theories applied and, more importantly, to deepen and broaden existing knowledge on a young and scarcely studied sector showing great potential, the Finnish biotechnology industry. The results of the empirical study based on regression analysis do not provide unconditional support for any of the frameworks. The evidence presented is only partially supportive. Reasons for this might be inherent in the general nature of the theories themselves as well as some unique characteristics of the biotech industry. – Biotechnology ; capital structure ; agency costs ; pecking order ; asymmetric information ; tradeoff theory – – Tämä tutkimus tarkastelee 59 suomalaisen bioteknologia-alalla toimivan pk-yrityksen poikkileikkausaineistoa kolmen eri teoreettisen viitekehyksen näkökulmasta, jotka pyrkivät selittämään rahoitusrakennevalintoja yritysorganisaatiossa. Teoreettiset lähestymistavat käsittävät päämies-agentti-ongelmaa, asymmetrista informaatiota sekä veroetuja. Tutkimuksen tarkoituksena on testata sovellettujen teorioiden validiteettia, mutta erityisesti syventää tietämystä nuoresta, niukasti tutkitusta bioteknologiasektorista. Regressioanalyysiin pohjautuva empiirinen tarkastelu ei tue yhtäkään viitekehystä sellaisenaan. Tulokset ovat vain joiltain osin teorioita tukevia. Tämän voidaan olettaa johtuvan teorioiden yleisluontoisuudesta sekä bioteknologiasektorin erityispiirteistä. – Bioteknologia ; rahoitusrakenne ; agenttikustannukset ; pecking order ; asymmetrinen informaatio ; trade-off teoria
Keywords: 330; Biotechnologie; Kapitalstruktur; Asymmetrische Information; Klein- und Mittelunternehmen; Biotechnische Industrie; Finnland